2009
DOI: 10.1016/j.geoforum.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding youth transition as ‘Becoming’: Identity, time and futurity

Abstract: Drawing on recent work in psychology, philosophy, and youth geographies, this article responds to calls for theoretical rigour in children's geographies by developing the concept of becoming for youth transitions research. Becoming has been used by psychologist Gordon Allport (1955) in his work on the proces-sual nature of personal identity, while Elizabeth Grosz (1999) has used the concept of becoming to explore conceptions of time as a lived experience, focusing on the dynamics of time as duration. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 51 publications
1
145
0
Order By: Relevance
“…Time is not a 'neutral medium', but plays an active role in the framing of life events (Worth, 2009, p.1055, see also Grosz, 1999. Perks and Thomson (2006, p.212) found that in the immediate aftermath of a trauma, interviewees were likely to offer a 'narrow viewpoint' as they struggled to make sense of their experiences.…”
Section: The Influence Of Time Passed: Contemporary Versus Retrospectmentioning
confidence: 99%
“…Time is not a 'neutral medium', but plays an active role in the framing of life events (Worth, 2009, p.1055, see also Grosz, 1999. Perks and Thomson (2006, p.212) found that in the immediate aftermath of a trauma, interviewees were likely to offer a 'narrow viewpoint' as they struggled to make sense of their experiences.…”
Section: The Influence Of Time Passed: Contemporary Versus Retrospectmentioning
confidence: 99%
“…More critical studies have advocated a relational approach, exploring the roles of families and peers (Hopkins and Pain 2007;Langevang 2008) and other generations (Tucker 2003), as well as contexts of poverty (van Blerk 2008) and recognising that the endpoint of transition may be 'negotiated interdependence' (Punch 2002) rather than independence. Broader relational concepts of lifecourse also allow for exploration of other events and transitions punctuating individuals' lives, beyond those examined in youth transition studies (Bailey 2009), including unexpected 'fateful moments' (Worth 2009), 'vital conjunctures' (Langevang 2008) and rites of passage (Teather 1999). These may contribute to a 'processual and non-linear transition' rather than neat transfers between distinct life stages (Langevang 2008(Langevang :2040.…”
Section: Space Time and Time-space In Young Livesmentioning
confidence: 99%
“…Few studies of lifecourse have engaged with explicit theorisations of temporality; most espouse a linear view of time (Worth 2009) and future orientation. Recent work has, however, engaged with non-linear conceptions of time to understand childhood as 'going on' rather than 'growing up' (Horton and Kraftl 2006), as 'being and becoming' (Uprichard 2008 As elsewhere in the world, children in southern Africa occupy and produce distinct time-spaces.…”
Section: Space Time and Time-space In Young Livesmentioning
confidence: 99%
See 2 more Smart Citations